Penguatan Karmaca (Karakter Gemar Membaca) Pada Anak Melalui Herakan Literasi Sekolah (GLS) di SDN No.56 Palilang - Wahyu Muh. Syata; Yustina Jimmy; Bellona Mardhatillah Sabillah (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The school literacy movement (GLS) is a comprehensive effort that involves all school members such as teachers, students, student guardians and the community as part of the education ecosystem. Literacy, which means being literate or being able to read, is a powerful weapon for changing the social status of a nation. Reading is not only understood to mean a series of letters, words, pharases and sentences but also “reading” in the sense of intrpreting a series of multidimensional life events. If educating means teaching how to interpret the entire journey of life, then educating means teaching how to read. The literacy skills of indonesian students are in a worryng condition, so one of the efforts made by the indonesian government through the ministry of educations and culture is to launch a literacy movement (GLS) the school literacy movement is a comprehensive effort to make schools a learning oerganization whose citizens are lifelong literate through public involvement. Students’ lack of awareness of reading results in the urgency of literacy needing to be instilled from elementary school age. Seeing that the condition of students’ literacy skills at SD Negeri 56 Palilang is still very poor, so there is a need for encouragement and continuous guidance to improve it, so that the service implements the habit of liking reading which aims to improve students’ literacy skills and can increase students’ interest in reading at SD Negeri 56 Palilang. This schools literation movement is designed so that students can realize how important it is for students to increase their interest in reading. To see the results of reading tutoring, we carry out an evaluation by giving one reading to students.